Efficiency of acoustic radiation force impulse imaging for the staging of graft fibrosis after liver transplantation. Issue 4 (2nd January 2019) - Yoshino, Kenji; Taura, Kojiro; Okuda, Yukihiro; Ikeno, Yoshinobu; Uemoto, Yusuke; Nishio, Takahiro; Yamamoto, Gen; Tanabe, Kazutaka; Koyama, Yukinori; Seo, Satoru; Kaido, Toshimi; Okajima, Hideaki; et al.
Abstract : Aim: Liver biopsy is the gold standard for assessing liver fibrosis (LF) after liver transplantation (LT), but its invasiveness limits its utility. This study aimed to evaluate the usefulness of liver stiffness measurement (LSM) using acoustic radiation force impulse (ARFI) imaging to assess LF after LT. Methods: Between September 2013 and January 2017, 278 patients who underwent liver biopsy after LT in Kyoto University Hospital (Kyoto, Japan) were prospectively enrolled. Liver stiffness measurement was carried out using ARFI imaging; its value was expressed as shear wave velocity (Vs) [m/s]. The LF was evaluated according to METAVIR score (F0–F4). The diagnostic performance of Vs for F2≤ and F3≤ was assessed and compared with that of laboratory tests using receiver operating characteristic (ROC) analysis. Results: The median Vs values increased according to the progression of LF (F0, 1.18 (0.78–1.92); F1, 1.35 (0.72–3.54); F2, 1.55 (1.05–3.37); F3, 1.84 (1.41–2.97)). The Vs had the highest area under the ROC curve (AUROC) for the prediction of both F2 ≤ and F3 ≤ fibrosis (F2, 0.77; and F3, 0.85). With the cut‐off value of Vs >1.31, sensitivity, specificity, positive predictive value, and negative predictive value were 89.4%, 53.3%, 37.3%, and 94.2% in predicting F2≤, respectively. Shear wave velocity diagnosed LF better than any laboratory tests regardless of the type of primary disease. Conclusions: Acoustic radiation force impulse helps to assess graft LF after LT. The high sensitivity suggested that ARFI might reduce the frequency of liver biopsies by detecting patients who are unlikely to have significant fibrosis after LT. (Unique trial no. UMIN R000028296.)